Penelitian ini bertujuan untuk Penerapan Pendekatan Reggio Emilia dalam Mengembangkan Keterampilan Berpikir Tinggi (HOTS) pada Anak Usia 5-6 Tahun di RA Nahdliyatul Islamiah - Sodiq, Jakfarus; Farida, Siti; Musayyadah (Institut Agama Islam Negeri Madura, 2026)
This study was conducted to examine how the Reggio Emilia Approach contributes to the development of Higher Order Thinking Skills (HOTS) in children aged 5–6 years. HOTS, which involve the abilities to analyze, evaluate, and create, need to be fostered from an early age to support children’s critical and creative thinking development. This research applied a qualitative descriptive design and was carried out at RA Nahdliyatul Islamiyah. The research participants included a classroom teacher and children in the 5–6 age group. Data were obtained through direct observation of learning activities, in-depth interviews with the teacher, and documentation of children’s learning processes and products. The data were then analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings indicated that learning activities based on the Reggio Emilia Approach, such as project work, exploration, and group discussion, were able to encourage the development of children’s higher-level thinking. Children demonstrated analytical skills when identifying and exploring objects, evaluative skills when expressing opinions, and creative skills when producing their own work. In addition, the teacher’s role as a facilitator and the provision of a supportive learning environment strengthened this development. It can be concluded that the Reggio Emilia Approach is effective in supporting the enhancement of HOTS in early childhood learning.